Suministro de energía eléctrica a partir de la energía solar fotovoltaica para el centro de producción e investigación Acraquia de la facultad de ciencias de ingeniería de la UNH - Navarro Daviran, John Fisher (2022)
It has been demonstrated that Peru has an excellent solar energy potential that are inexhaustible energy sources. The proposed problem is how to meet the basic needs of electricity from solar photovoltaic energy to improve the living conditions of the people of the Center for Production and Research Acraquia of the UNH?. Our project was developed by correctly locating the angle of inclination and orientation of solar panels, the review of the solar map of the place of interest and solar radiation data obtained from the NASA website. We calculated daily, monthly, quarterly, semi-annual and annual solar radiation data confirming and demonstrating that the solar radiation at the coordinates of our project location is 5.22 kWh/m2, sufficient and constant energy. This allowed to clarify and optimize the information confirming the objective and the optimization of the project execution by having and counting with adequate solar energy facilities validating our hypothesis of satisfying the basic electricity needs to improve the living conditions of the settler being a clean energy that will minimize the negative impacts on the environment. In this research project we have used the observation and experimental method and statistical techniques.